2022
DOI: 10.3390/rs14030791
|View full text |Cite
|
Sign up to set email alerts
|

Development of an App and Teaching Concept for Implementation of Hyperspectral Remote Sensing Data into School Lessons Using Augmented Reality

Abstract: For the purpose of expanding STEM (science, technology, engineering, mathematics) education with remote sensing (RS) data and methods, an augmented reality (AR) app was developed in combination with a worksheet and lesson plan. Data from the Hyperspectral Imager for the Coastal Ocean (HICO) was searched for topics applicable to STEM curricula, which was found in the example of a harmful algal bloom in Lake Erie, USA, in 2011. Spectral shape algorithms were applied to differentiate between less harmful green an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…• Kao and Ruan (2022), Lindner et al (2022), andCampos et al (2022) found increased engagement and performance through interactive AR modes and applications in programming and environmental science.…”
Section: • Nadan Et Al (2011) Utilized Vr Technologies Like Cave Andmentioning
confidence: 99%
“…• Kao and Ruan (2022), Lindner et al (2022), andCampos et al (2022) found increased engagement and performance through interactive AR modes and applications in programming and environmental science.…”
Section: • Nadan Et Al (2011) Utilized Vr Technologies Like Cave Andmentioning
confidence: 99%
“…Unity is a powerful, versatile, and popular game development engine that provides a sandbox environment for the creation of immersive and interactive 2D and 3D experiences. Unity (versions 2019-2022.3 used during development) offers exceptional crossplatform capabilities, including mobile devices, consoles, and desktops, and it supports emerging technologies such as AR (e.g., [30][31][32][33]) and VR, which were used by the Satel-liteSkill5 app; many of these AR examples were carried out with public engagement [34,35] or education and capacity building [36,37] in mind. The user interface that Unity provides significantly simplifies the game development process without the developer needing extensive coding knowledge.…”
Section: Development Enginementioning
confidence: 99%
“…It is, however, solely focused on geography lessons. Another recent approach to integrating remote sensing into classrooms makes use of the BYOD (Bring Your Own Device) concept, integrating the capabilities of pupil's smartphones in learning experiences based on augmented reality (Lindner et al 2019(Lindner et al , 2022López Núñez et al 2020;Rienow et al 2020). While they show promising capabilities and offer interesting approaches to even include topics like hyperspectral imaging in classrooms (Lindner et al 2022) they are limited in terms of computational capacities of the devices used.…”
Section: Related Workmentioning
confidence: 99%